2016
DOI: 10.1002/ece3.2293
|View full text |Cite
|
Sign up to set email alerts
|

Both morph‐ and species‐dependent asymmetries affect reproductive barriers between heterostylous species

Abstract: The interaction between floral traits and reproductive isolation is crucial to explaining the extraordinary diversity of angiosperms. Heterostyly, a complex floral polymorphism that optimizes outcrossing, evolved repeatedly and has been shown to accelerate diversification in primroses, yet its potential influence on isolating mechanisms remains unexplored. Furthermore, the relative contribution of pre‐ versus postmating barriers to reproductive isolation is still debated. No experimental study has yet evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 147 publications
(352 reference statements)
1
37
1
Order By: Relevance
“…2), pollinators may not be able to distinguish between flowers of different Pulmonaria species in sympatric populations, which creates opportunities for interspecific gene flow and hybridization. Keller et al (2012Keller et al ( , 2016 investigated whether differences in reciprocity affected possibilities for gene flow among three distylous Primula species. Their results showed that interspecific decrease of reciprocity between high sexual organs of complementary floral morphs limited interspecific pollen transfer from anthers of shortstyled flowers to stigmas of long-styled flowers.…”
Section: Reciprocity and Maintenance Of Species Boundariesmentioning
confidence: 99%
“…2), pollinators may not be able to distinguish between flowers of different Pulmonaria species in sympatric populations, which creates opportunities for interspecific gene flow and hybridization. Keller et al (2012Keller et al ( , 2016 investigated whether differences in reciprocity affected possibilities for gene flow among three distylous Primula species. Their results showed that interspecific decrease of reciprocity between high sexual organs of complementary floral morphs limited interspecific pollen transfer from anthers of shortstyled flowers to stigmas of long-styled flowers.…”
Section: Reciprocity and Maintenance Of Species Boundariesmentioning
confidence: 99%
“…However, several studies found herkogamy to have a strong genetic basis (e.g., Herlihy and Eckert 2007;Luo and Widmer 2013), and a comprehensive review concluded that the trait is typically highly heritable and evolvable (Opedal et al 2017). Moreover, the profound functional implications of sexual organ position Keller et al 2012Keller et al , 2014Keller et al , 2016) justify speculating about possible adaptive explanations for the existence of high-herkogamous plants.…”
Section: Simultaneous Effects On Number Of Seeds and Mating Mode Of Smentioning
confidence: 99%
“…He found low pollen fertility, which is common in hybrids, in many of what appeared to be pure species, indicating that the individuals were in fact backcrossed hybrids. Keller et al (2016) found that the reproductive barriers upholding species integrity were weakened in the hybrids, allowing for introgression, especially in P. elatior. This is in accordance with our findings; that even though the three sympatric species on Møn appear pure, many of the investigated markers pointed to backcrossing and introgression.…”
Section: Genetic Composition Of Species and Their Hybridsmentioning
confidence: 99%
“…The difference in inflorescence morphology may play a role, since the solitary flower raised on a pedicel allows P. vulgaris to develop and open its flowers relatively quickly in its open, sun-exposed, warm localities, where P. vulgaris occupies a different niche than P. elatior, which is found in shadier locations. Keller et al (2016) modelled the reproductive barriers between P. vulgaris and P. elatior in a series of experiments to evaluate pre-and postmating barriers and the significance of the heteromorphic flowers. They found that the types of floral morphs involved in the crosses also played a part in fertility.…”
Section: Species Boundariesmentioning
confidence: 99%